إسهامات مولود معمري في الانثروبولوجيا - كرام, يسين (Changement Social; No 4 (2018): revue change social, 2018)
مولودمعمري،شعلةفكريةبامتياز. جمعبينالأدبواللسانياتوالأنثروبولوجيا. وعلىالرغممنأنهذهالميادينالفكريةالثلاثعندهممتزجةومتداخلةفيمابينهاومنالعسيرفصلبعضهاعنبعض،إلاأنهذهالورقةالبحثيةهدفهافقطهوالإشارةإلىإسهاماتمعمريفيالانثروبولوجيادونسلخهاتاماعنأعمالهالأدبيةواللسانية. ولماكانمعمريالأنثروبولوجيلميكتشفبعدفإنهذهالدراسةلاتطمحأكثرمنلفتالانتباهإلىهذهالشعلةالفكريةوإسهاماتهاالأنثروبولوجية. Mouloud Mammeri is an intellectual flame of excellence. He combined between literature linguistics and anthropology. Although are intertwined and interrelated, this paper is only intended to refer to the contributions of Mammeri anthropology without being completely stripped of his literary and linguistic works. As he was not discorvered, this study does not aspire more than drawing attention to this intllectual and its anthropological conributions.